Collateral Circulation in Thrombectomy for Stroke After 6 to 24 Hours in the DAWN Trial - Liebeskind, David S.; Saber, Hamidreza; Xiang, Bin; Jadhav, Ashutosh P.; Jovin, Tudor G.; Haussen, Diogo C.; Budzik, Ronald F.; Bonafe, Alain; Bhuva, Parita; Yavagal, Dileep R.; Hanel, Ricardo A.; Ribo, Marc; et al. (Stroke (1970), 2022)
Collaterals govern the pace and severity of cerebral ischemia, distinguishing fast or slow progressors and corresponding therapeutic opportunities. The fate of sustained collateral perfusion or collateral failure is poorly characterized. We evaluated the nature and impact of collaterals on outcomes in the late time window DAWN trial (Diffusion-Weighted Imaging or Computed Tomography Perfusion Assessment With Clinical Mismatch in the Triage of Wake-Up and Late Presenting Strokes Undergoing Neurointervention With Trevo). The DAWN Imaging Core Lab prospectively scored collateral grade on baseline computed tomography angiography (CTA; endovascular and control arms) and digital subtraction angiography (DSA; endovascular arm only), blinded to all other data. CTA collaterals were graded with the Tan scale and DSA collaterals were scored by ASITN grade (American Society of Interventional and Therapeutic Neuroradiology collateral score). Descriptive statistics characterized CTA collateral grade in all DAWN subjects and DSA collaterals in the endovascular arm. The relationship between collateral grade and day 90 outcomes were separately analyzed for each treatment arm. Collateral circulation to the ischemic territory was evaluated on CTA (n=144; median 2, 0-3) and DSA (n=57; median 2, 1-4) before thrombectomy in 161 DAWN subjects (mean age 69.8±13.6 years; 55.3% women; 91 endovascular therapy, 70 control). CTA revealed a broad range of collaterals (Tan grade 3, n=64 [44%]; 2, n=45 [31%]; 1, n=31 [22%]; 0, n=4 [3%]). DSA also showed a diverse range of collateral grades (ASITN grade 4, n=4; 3, n=22; 2, n=27; 1, n=4). Across treatment arms, baseline demographics, clinical variables except atrial fibrillation (41.6% endovascular versus 25.0% controls, =0.04), and CTA collateral grades were balanced. Differences were seen across the 3 levels of collateral flow (good, fair, poor) for baseline National Institutes of Health Stroke Scale, blood glucose <150, diabetes, previous ischemic stroke, baseline and 24-hour core infarct volume, baseline and 24-hour Alberta Stroke Program Early CT Score, dramatic infarct progression, final Thrombolysis in Cerebral Infarction 2b+, and death. Collateral flow was a significant predictor of 90-day modified Rankin Scale score of 0 to 2 in the endovascular arm, with 43.7% (31/71) of subjects with good collaterals, 30.8% (16/52) of subjects with fair collaterals, and 17.7% (6/34) of subjects with poor collaterals reaching modified Rankin Scale score of 0 to 2 at 90 days ( =0.026). DAWN subjects enrolled at 6 to 24 hours after onset with limited infarct cores had a wide range of collateral grades on both CTA and DSA. Even in this late time window, better collaterals lead to slower stroke progression and better functional outcomes. Registration: URL: https://www.clinicaltrials.gov; Unique identifier: NCT02142283.